Aplicativo web para pessoas físicas intituladas atiradores, colecionadores, caçadores e cidadão comum que utilizam produto controlado pelo exército brasileiro e polícia federal - Paula, Allan Francis de (2015)
This work presents a proposal of a web application to facilitate the access of individuals in the acquisition of firearms and controlled inputs and supervi sed by federal agencies Brazilian Army and Federal Police, where the functional structure of these institutions to reach to be updated, but still on track to be appropriate, the costs of running technical and bureaucratic order through its internal section s still largely with physical and not digital processes. There are two distinct universes supervised as the nature of the activity: 1) Corporations: manufacture, import, export, customs clearance, marketing and traffic; 2) Individuals: practicing target shooting, collectors weapons, ammunition, vehicles, airplanes, etc., practitioners of legalized hunting and citizens who just want possession of a firearm, aimed at individual and familial security. The web application developed in this work has as its objec t the universe of individuals, given the fact that due to the large amount of existing legislation on the subject, raises many questions about the procedures. Thus, the intention of this work is to facilitate access through an interactive environment with minimal effort by the person concerned. For application development, we opted for the PHP language, tied to HTML, CSS and the FrameWork CodeIgniter.